2014
DOI: 10.1371/journal.pone.0094630
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Responses Associated with a Human-Mediated Predator Shelter

Abstract: Human activities in protected areas can affect wildlife populations in a similar manner to predation risk, causing increases in movement and vigilance, shifts in habitat use and changes in group size. Nevertheless, recent evidence indicates that in certain situations ungulate species may actually utilize areas associated with higher levels of human presence as a potential refuge from disturbance-sensitive predators. We now use four-years of behavioral activity budget data collected from pronghorn (Antilocapra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 47 publications
4
51
1
Order By: Relevance
“…Our results showed that some lactating females left areas near a trail when hikers were frequent, but those that stayed were less vigilant within the 500‐m threshold distance from trails. This 500‐m threshold is relatively consistent with other studies of ungulates that have reported a human‐induced refuge from predators (Berger, ; Shannon et al., ). Although coyotes and black bears were found to use trails and gravel roads more often than expected based on random locations in our study area (see Gaudry, ; a companion study conducted in the Gaspésie National Park), the automated camera traps distributed along the hiking trails showed that no coyote and only a few black bears used trails in the hour following the passage of a hiker (F. Lesmerises & M.‐H.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results showed that some lactating females left areas near a trail when hikers were frequent, but those that stayed were less vigilant within the 500‐m threshold distance from trails. This 500‐m threshold is relatively consistent with other studies of ungulates that have reported a human‐induced refuge from predators (Berger, ; Shannon et al., ). Although coyotes and black bears were found to use trails and gravel roads more often than expected based on random locations in our study area (see Gaudry, ; a companion study conducted in the Gaspésie National Park), the automated camera traps distributed along the hiking trails showed that no coyote and only a few black bears used trails in the hour following the passage of a hiker (F. Lesmerises & M.‐H.…”
Section: Discussionsupporting
confidence: 90%
“…This may occur even in parks where human activities are highly regulated (Whittington, St. Clair, & Mercer, ). In such cases, prey can modulate predation risk by exploiting the enemy‐free spaces created when the presence of humans and associated infrastructure displaces predators (i.e., the refuge hypothesis ) (Berger, ; Shannon, Cordes, Hardy, Angeloni, & Crooks, ; Steyaert et al., ). Predation risk varies in space and time, and thus, antipredator strategies should be adaptable to variation in risk.…”
Section: Introductionmentioning
confidence: 99%
“…Such a possibility has been raised under circumstances where human harvesting of top predators hinders predators' ability to perform functional ecological roles (Ordiz et al, 2013). Human activity can also alter trophic cascades when prey use human presence as a refuge from predation (Shannon et al, 2014). Here we propose that this possibility be extended to circumstances where top predators focus on humanprovided foods, rather than on co-occurring predators and prey, and even more so where human-wildlife conflict leads to high rates of mortality of top predators.…”
Section: Discussionmentioning
confidence: 99%
“…Urban predators may also supplement their diet through anthropogenic resources which would reduce their need to hunt risky prey and further reduce their impact on prey populations (Morey, Gese, & Gehrt, ; Murray & St. Clair, ). In many cases, larger‐bodied predators avoid areas of high human activity (e.g., Shannon, Cordes, Hardy, Angeloni, & Crooks, ; Waser et al., ). However, some predators have adapted behaviours that allow them to persist in human‐dominated ecosystems—for example, increased nocturnality (Gaynor, Hojnowski, Carter, & Brashares, ).…”
Section: Introductionmentioning
confidence: 99%